2017
DOI: 10.1016/j.jacl.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell polyunsaturated fatty acids and mortality in the Women's Health Initiative Memory Study

Abstract: Background The prognostic value of circulating polyunsaturated fatty acid (PUFA) levels is 4unclear. Objectives To determine the associations between red blood cell (RBC) PUFA levels and risk for death. Methods This prospective cohort study included 6501 women aged 65–80 who participated in the Women’s Health Initiative Memory Study (enrolment began 1996). RBC PUFA levels were measured at baseline and expressed as a percent of total RBC PUFAs. PUFAs of primary interest were the n-3 PUFAs eicosapentaenoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 73 publications
(82 reference statements)
5
55
0
4
Order By: Relevance
“…Such strong correlations suggest little added contribution of DPA to the predictive value of the O3I. Consistent with this, addition of DPA did not significantly improve the mortality risk prediction of the O3I in the Women's Health Initiative Memory Study [24]. Although a growing body of evidence suggests that DPA may be a highly bioactive compound, studies are needed to dissect out its contribution to CHD risk from that of EPA and DHA, which are also strongly correlated with CHD risk [25].…”
Section: Discussionmentioning
confidence: 56%
“…Such strong correlations suggest little added contribution of DPA to the predictive value of the O3I. Consistent with this, addition of DPA did not significantly improve the mortality risk prediction of the O3I in the Women's Health Initiative Memory Study [24]. Although a growing body of evidence suggests that DPA may be a highly bioactive compound, studies are needed to dissect out its contribution to CHD risk from that of EPA and DHA, which are also strongly correlated with CHD risk [25].…”
Section: Discussionmentioning
confidence: 56%
“…We recently reported similar findings to these in the Women’s Health Initiative Memory Study where there was a significant inverse trend across quartiles of the Omega-3 Index for total mortality, with the highest quartile being at 22% lower risk for death compared with the lowest. 20 That study followed a nationwide sample of 6500, approximately 70-year-old women for 15 years. Kleber et al also found a 9% decrease in risk for all-cause mortality per 1 SD increase in the Omega-3 Index after 10 years of follow-up in 3259 German CHD patients.…”
Section: Resultsmentioning
confidence: 99%
“…An 11% reduction (per 1 SD increase in the Omega-3 Index) in risk for death from other causes was also seen in the women’s study mentioned previously. 20 It is unclear what mechanism might explain this observation; but since n-3 PUFAs are known to have a wide variety of effects on cell membrane biology, 25 , 26 a systemic impact of higher levels of these FAs on overall cellular health is possible. As noted earlier, several recent randomized trials of fish oil with total mortality as an endpoint have been null, but they typically showed trends toward a benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported the fatty acid profile in red blood cells or in plasma/serum phospholipids (PL). Among the 24 studies, studies reported the omega-3 index only and showed that it was higher in older participants [37][38][39][40][41][42][43] . Two studies on the omega-3 index reported an increase of about 5-7% of the omega-3 index every decade 37,41 .…”
Section: Without An Omega-3 Fatty Acid Supplementationmentioning
confidence: 99%